Igarapé-Miri: a passagem da escravidão ao trabalho livre, numa região de engenhos (Grão-Pará: 1843-1888) - NASCIMENTO, Sônia Viana do (Universidade Federal do Pará, 2018)
In Igarapé-Miri, throughout the nineteenth century, the presence of slave workers was significant and of great relevance to the activities of sugarcane cultivation and the production of aguardente / cachaça. The present dissertation analyzes the transition from slavery to free labor, emphasizing that the proximity or the end of slavery did not mean the exit of the slave laborers from the sugar mills of the region. From the use of various sources such as newspapers, post-mortem inventories, Igarapé-Miri municipal council balance, labor contracts, and others, demographic data we understand the importance of slavery in the place and the mechanisms used by the lords to ensure the hand Of work.